Police in the Hallways : Discipline in an Urban High School - Nolan, Kathleen (Book collections on Project MUSE., 2011)
As zero-tolerance discipline policies have been instituted at high schools across the country, police officers are employed with increasing frequency to enforce behavior codes and maintain order, primarily at poorly performing, racially segregated urban schools. Actions that may once have sent students to the detention hall or resulted in their suspension may now introduce them to the criminal justice system. In "Police in the Hallways," Kathleen Nolan explores the impact of policing and punitive disciplinary policies on the students and their educational experience. Through in-depth.